Rickettsia 'in' and 'out': two different localization patterns of a bacterial symbiont in the same insect species. - Ayelet Caspi-Fluger (Public Library of Science (PLoS), 2011)
Intracellular symbionts of arthropods have diverse influences on their hosts, and their functions generally appear to be associated with their localization within the host. The effect of localization pattern on the role of a particular symbiont cannot normally be tested since the localization pattern within hosts is generally invariant. However, in Israel, the secondary symbiont Rickettsia is unusual in that it presents two distinct localization patterns throughout development and adulthood in its whitefly host, Bemisia tabaci (B biotype). In the "scattered" pattern, Rickettsia is localized throughout the whitefly hemocoel, excluding the bacteriocytes, where the obligate symbiont Portiera aleyrodidarum and some other secondary symbionts are housed. In the "confined" pattern, Rickettsia is restricted to the bacteriocytes. We examined the effects of these patterns on Rickettsia densities, association with other symbionts (Portiera and Hamiltonella defensa inside the bacteriocytes) and on the potential for horizontal transmission to the parasitoid wasp, Eretmocerus mundus, while the wasp larvae are developing within the whitefly nymph. Sequences of four Rickettsia genes were found to be identical for both localization patterns, suggesting that they are closely related strains. However, real-time PCR analysis showed very different dynamics for the two localization types. On the first day post-adult emergence, Rickettsia densities were 21 times higher in the "confined" pattern vs. "scattered" pattern whiteflies. During adulthood, Rickettsia increased in density in the "scattered" pattern whiteflies until it reached the "confined" pattern Rickettsia density on day 21. No correlation between Rickettsia densities and Hamiltonella or Portiera densities were found for either localization pattern. Using FISH technique, we found Rickettsia in the gut of the parasitoid wasps only when they developed on whiteflies with the "scattered" pattern. The results suggest that the localization pattern of a symbiont may influence its dynamics within the host.